Corrosion-resistant steel slag modified steel structure fireproof coating

By introducing steel slag and modified expanded perlite into steel structure fire-retardant coatings, the shortcomings of existing coatings in terms of durability and corrosion resistance are solved, and higher fire resistance, corrosion resistance and durability are achieved, while reducing costs.

CN119662072AActive Publication Date: 2025-03-21FUZHOU UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411420727.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-03-21
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

The existing steel structure fire-resistant coatings have problems such as poor durability, easy corrosion, and high cost during construction. In particular, the large shrinkage of the slag leads to cracking of the paint, and lightweight porous materials increase the corrosion risk of the steel structure.

Method used

Corrosive slag-resistant steel structure fire-retardant coatings are used, and their formulations include bonding materials, modified lightweight refractory materials, flame retardant materials, anhydrous sodium sulfate, VAE latex, water, anti-shrinkage agents and heat stabilizers. By introducing steel slag as a shrinkage agent and adsorbing benzotriazole on the expanded perlite pore walls by vacuum conditions, the corrosion resistance of the paint is enhanced.

Benefits of technology

It significantly improves the fire resistance, corrosion resistance and durability of fire-resistant coatings, reduces the shrinkage phenomenon of coatings, enhances adhesion and long-term durability, and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a corrosion-resistant steel slag modified steel structure fireproof coating, which is prepared from the following raw materials in parts by weight: 90 to 150 parts of binding materials, 320 to 360 parts of modified lightweight refractory materials, 30 to 60 parts of flame-retardant materials, 3.75 to 7.5 parts of anhydrous sodium sulfate, 150 to 210 parts of VAE latex, 420 to 480 parts of water, 0 to 70 parts of anti-shrinking agents and 13.5 parts of heat stabilizers. The industrial waste steel slag is used as an anti-shrinking agent of the fireproof coating, so that the shrinkage of the fireproof coating is effectively reduced, the fire-resistant time, cohesiveness, durability and other properties of the coating are improved, and the fireproof coating has important significance for protecting the environment and reducing pollution; meanwhile, the modified expanded perlite used in the invention is prepared by adsorbing an environment-friendly corrosion inhibitor benzotriazole on the pore wall of the expanded perlite under a vacuum condition, and the influence of benzotriazole on hydration of the binding material is reduced, so that the corrosion inhibition efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fireproof and anticorrosion coating on steel structure surfaces, and specifically relates to a corrosion-resistant steel slag modified steel structure fireproof coating. Background Art

[0002] In recent years, steel structures have been widely used in high-rise and long-span buildings due to their light weight, high strength, excellent earthquake resistance and convenient construction characteristics. However, the performance of steel is sensitive to temperature changes, especially when the ambient temperature rises to about 250°C, its impact toughness will decrease; if the temperature continues to rise to 300°C, the yield and ultimate strength of the steel will drop significantly. In view of the frequent occurrence of building fire accidents, which cause huge losses to personnel safety and the national social economy, it is particularly important to strengthen the fire protection of steel structures. Therefore, the development of effective steel structure fire retardant coatings is of great significance to improving building fire safety.

[0003] In practical applications, steel structures must not only resist the threat of fire, but also prevent damage caused by corrosion. Corrosion on the surface of steel will weaken the adhesion between the fire retardant coating and the steel, causing the coating to fall off, thereby losing its protective effect on the steel structure. Severe corrosion will also reduce the cross-sectional area of ​​the steel structure, causing it to fail brittlely due to external forces without significant deformation. Therefore, it is crucial to implement effective anti-corrosion measures for steel structures. At present, spraying anti-corrosion coatings is a direct and simple protection method that can provide the necessary anti-corrosion protection for steel structures.

[0004] At present, during the construction of fire retardant coatings for steel structures, in order to make the steel structure have a certain degree of corrosion resistance, a layer of anti-corrosion primer will be applied on the surface of the steel structure before the fire retardant coating is applied, and the cementitious material is usually based on silicate cement. Although it has a certain effect, there are still many problems.

[0005] 1. Traditional non-expansive steel structure fire retardant coatings mainly use slag cement as the cementitious material. However, slag has the characteristics of large shrinkage and is prone to cracking, which seriously affects the durability of non-expansive steel structure fire retardant coatings; 2. Non-expandable steel structure fire retardant coatings use a lot of lightweight and porous thermal insulation materials, which results in a large porosity of the fire retardant coating, allowing moisture and air to easily contact the steel structure, causing corrosion of the steel structure; 3. A common method to avoid corrosion of steel structures is to apply corrosion inhibitors before coating, but this also leads to increased costs.

[0006] Steel slag is a byproduct of the steelmaking process, usually accounting for 10% to 20% of steel production, but its recycling rate is only 30%. A large amount of steel slag is piled up as waste, which has a serious impact on the environment. Therefore, there is an urgent need to recycle these steel slag resources to solve environmental pollution problems and promote resource recovery and energy conservation. The hydration characteristics of steel slag and its products are similar to those of cement, which makes steel slag a research focus for cement substitutes. When used in combination with other mineral admixtures, steel slag helps to enhance the mechanical properties and durability of fire retardant coatings.

[0007] Therefore, in order to improve the corrosion resistance, fire resistance time, shrinkage resistance and durability of fire retardant coatings, a corrosion-resistant steel slag modified steel structure fire retardant coating is designed, which is of great significance to improving the work efficiency in the steel structure application field and the application and promotion of corrosion-resistant fire retardant coatings. Summary of the invention

[0008] The purpose of the present invention is to provide a corrosion-resistant steel slag modified steel structure fire retardant coating, which can significantly improve the fire resistance time, corrosion resistance and durability of non-expanding steel structure fire retardant and anti-corrosion coatings, and play a positive role in promoting the promotion and application of non-expanding steel structure fire retardant and anti-corrosion coatings.

[0009] In order to achieve the above object, the present invention adopts the following technical solution: A corrosion-resistant steel slag modified steel structure fire-retardant coating, the raw materials used and the usage thereof are, by weight: 90-150 parts of bonding material, 320-360 parts of modified lightweight refractory material, 30-60 parts of flame retardant material, 3.75-7.5 parts of anhydrous sodium sulfate, 150-210 parts of VAE latex, 420-480 parts of water, 0-70 parts of anti-shrinkage agent and 13.5 parts of heat stabilizer.

[0010] Furthermore, the bonding material consists of slag and cement in a mass ratio of 7:3.

[0011] Furthermore, the modified lightweight refractory material is composed of expanded vermiculite, modified expanded perlite and fly ash hollow microspheres in a mass ratio of 36:33:31.

[0012] Furthermore, the modified expanded perlite is prepared by soaking the dried expanded perlite in a benzotriazole solution with a mass concentration of 2% under vacuum conditions for 30 minutes, adsorbing the benzotriazole on the pore wall of the expanded perlite through vacuum high pressure, and then drying for 24 hours; wherein the mass ratio of the expanded perlite to benzotriazole is 118.8:9.

[0013] Furthermore, the flame retardant material is aluminum hydroxide.

[0014] Furthermore, the anti-shrinkage agent is steel slag.

[0015] Furthermore, the thermal stabilizer is hydrotalcite.

[0016] Furthermore, the preparation method of the corrosion-resistant steel slag modified steel structure fire retardant coating comprises the following steps: (1) Preparation of component A: Place the bonding material, anhydrous sodium sulfate, expanded vermiculite, fly ash hollow microspheres, flame retardant material, and heat stabilizer into a mixer in sequence, stir and mix at room temperature at a speed of 140 r / min for 2 min to uniformly mix, and obtain component A; (2) Preparation of component B: Stir water and VAE latex at room temperature at a speed of 140-200 r / min and add anti-shrinkage agent, then continue stirring and mixing for 2 min to make the materials uniform, thereby obtaining component B; (3) Preparation of corrosion-resistant steel slag modified steel structure fire retardant coating: Stir components A and B at a speed of 140-200 r / min at room temperature and add modified expanded perlite, then continue stirring for 5 min.

[0017] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention effectively reduces the shrinkage of fire-retardant coatings by introducing steel slag as an anti-shrinkage agent, thereby improving the adhesion and long-term durability of the coatings; at the same time, the sulfides and oxides in the steel slag can play a positive role in the cement hydration process, further enhancing the fire resistance of the coatings. These improvements jointly improve the effectiveness of fire-retardant coatings in protecting steel structures. Specifically, the sulfides in the steel slag (generally 1-3%) can react with the hydroxide ions in the cement to form sulfoaluminates, and are converted into water-insoluble substances in the coating, which not only reduces the shrinkage of the coating, but also improves its fire resistance.

[0018] 2. The present invention uses vacuum conditions to adsorb benzotriazole on the pore wall of expanded perlite to reduce the effect of benzotriazole on the hydration of the bonding material, thereby enhancing the corrosion resistance of the fire retardant coating and extending its protection period for the steel structure. In addition, since benzotriazole is a mixed corrosion inhibitor, it can react with related ions in the medium to form an anti-corrosion precipitation film on the metal surface, so it is not necessary to paint before coating, reducing costs. DETAILED DESCRIPTION

[0019] A corrosion-resistant steel slag modified steel structure fire-retardant coating, the raw materials used and the usage thereof are, by weight: 90-150 parts of bonding material, 320-360 parts of modified lightweight refractory material, 30-60 parts of flame retardant material, 3.75-7.5 parts of anhydrous sodium sulfate, 150-210 parts of VAE latex, 420-480 parts of water, 0-70 parts of anti-shrinkage agent and 13.5 parts of heat stabilizer.

[0020] Wherein, the bonding material consists of slag and cement in a mass ratio of 7:3.

[0021] The modified lightweight refractory material is composed of expanded vermiculite, modified expanded perlite and fly ash hollow microspheres in a mass ratio of 36:33:31.

[0022] Specifically, the slag is ordinary blast furnace slag (S95), the cement is P·O 42.5 ordinary Portland cement. The diameter of the expanded vermiculite is 1 mm to 3 mm, and the bulk density is 90 kg / m 3 The diameter of the expanded perlite is 0.5 mm to 1 mm, and the bulk density is 84 kg / m 3 The diameter of the fly ash hollow microspheres is 0.3 mm to 0.45 mm, and the bulk density is 418.8 kg / m 3 , the thermal conductivity is 0.063~0.114 W / (m·K). The steel slag is industrial waste steel slag.

[0023] A method for preparing a corrosion-resistant steel slag modified steel structure fire retardant coating comprises the following steps: (1) Preparation of component A: Place the bonding material, anhydrous sodium sulfate, expanded vermiculite, fly ash hollow microspheres, flame retardant material, and heat stabilizer into a mixer in sequence, stir and mix at room temperature at a speed of 140 r / min for 2 min to uniformly mix, and obtain component A; (2) Preparation of component B: Stir water and VAE latex at room temperature at a speed of 140-200 r / min and add anti-shrinkage agent, then continue stirring and mixing for 2 min to make the materials uniform, thereby obtaining component B; (3) Preparation of component C: Soak the dried expanded perlite in a 2% benzotriazole solution under vacuum for 30 minutes, and then dry it in an oven for 24 hours. The modified expanded perlite obtained is used as component C; the mass ratio of the expanded perlite to benzotriazole is 118.8:9. ; (4) Preparation of corrosion-resistant steel slag modified steel structure fire retardant coating: Components A and B were stirred at a speed of 140-200 r / min at room temperature and component C was added. The mixture was then stirred for 5 min to obtain a corrosion-resistant steel slag modified steel structure fire retardant coating.

[0024] The present invention provides a slag-steel slag-based steel structure fireproof and anticorrosive integrated coating and a preparation method thereof. To further illustrate the technical means and effects adopted by the present invention, the present invention is described in detail below in conjunction with specific implementation methods, but the present invention is not limited thereto.

[0025] Embodiment 1: In this embodiment, the raw material ratio of a corrosion-resistant steel slag modified steel structure fire retardant coating is as follows by weight: 105 parts of bonding material, 360 parts of lightweight refractory material, 51.3 parts of flame retardant material, 7.5 parts of anhydrous sodium sulfate, 180 parts of VAE latex, 480 parts of tap water, 45 parts of anti-shrinkage agent and 13.5 parts of thermal stabilizer.

[0026] The bonding material consists of 75 parts of slag and 30 parts of cement.

[0027] The anti-shrinkage agent consists of 45 parts of steel slag.

[0028] The lightweight refractory material is composed of 129.6 parts of expanded vermiculite, 118.8 parts of expanded perlite and 111.6 parts of fly ash hollow microspheres.

[0029] The flame retardant material consists of 51.3 parts of aluminum hydroxide.

[0030] The heat stabilizer consisted of 13.5 parts of hydrotalcite.

[0031] In this embodiment, a corrosion-resistant steel slag modified steel structure fire retardant coating is prepared according to the following steps: Step 1: Weigh 105 parts of slag, 30 parts of cement, 7.5 parts of anhydrous sodium sulfate, 129.6 parts of expanded vermiculite, 118.8 parts of expanded perlite, 111.6 parts of fly ash hollow microspheres, 51.3 parts of aluminum hydroxide, and 13.5 parts of hydrotalcite, put them into a mixer in sequence, adjust the mixer speed to 140 r / min, stir and mix at room temperature for 2 min to make it evenly mixed, and obtain component A; Step 2: Weigh 480 parts of tap water and 180 parts of VAE latex, stir at room temperature at a speed of 140-200 r / min and add 45 parts of steel slag, then continue stirring and mixing for 2 minutes to make the materials uniform, to obtain component B; Step 3: Pour component B into component A and stir for 5 minutes to obtain the corrosion-resistant steel slag modified steel structure fire retardant coating.

[0032] Embodiment 2: In this embodiment, the raw material ratio of a corrosion-resistant steel slag modified steel structure fire retardant coating is as follows by weight: 105 parts of bonding material, 360 parts of lightweight refractory material, 51.3 parts of flame retardant material, 7.5 parts of anhydrous sodium sulfate, 180 parts of VAE latex, 480 parts of tap water, 45 parts of anti-shrinkage agent and 13.5 parts of thermal stabilizer.

[0033] The bonding material consists of 75 parts of slag and 30 parts of cement.

[0034] The anti-shrinkage agent consists of 45 parts of steel slag.

[0035] The modified lightweight refractory material is composed of 129.6 parts of expanded vermiculite, 118.8 parts of modified expanded perlite and 111.6 parts of fly ash hollow microspheres. The modified expanded perlite is made of benzotriazole and expanded perlite in a mass ratio of 9:118.8.

[0036] The flame retardant material consists of 51.3 parts of aluminum hydroxide.

[0037] The heat stabilizer consisted of 13.5 parts of hydrotalcite.

[0038] In this embodiment, a corrosion-resistant steel slag modified steel structure fire retardant coating is prepared by the following steps: Step 1: weigh 75 parts of slag, 30 parts of cement, 7.5 parts of anhydrous sodium sulfate, 129.6 parts of expanded vermiculite, 111.6 parts of fly ash hollow microspheres, 51.3 parts of aluminum hydroxide, and 13.5 parts of hydrotalcite, put them into a mixer in sequence, adjust the mixer speed to 140 r / min, stir and mix at room temperature for 2 min to make them evenly mixed, and obtain component A; Step 2: Weigh 480 parts of tap water and 180 parts of VAE latex, stir and add 45 parts of steel slag at a speed of 140-200 r / min at room temperature, and then continue to stir and mix for 2 minutes to evenly mix the materials to obtain component B; Step 3: Weigh benzotriazole and expanded perlite in proportion, first dissolve benzotriazole in an appropriate amount of water to obtain a 2% benzotriazole aqueous solution, then immerse the expanded perlite in the benzotriazole aqueous solution under vacuum conditions for 30 minutes, adsorb benzotriazole on the pore wall of the expanded perlite through vacuum high pressure, and then put it in an oven to dry for 24 hours to obtain component C; Step 4: Stir components A and B at a speed of 140-200 r / min and add 118.8 parts of component C at the same time, and stir for 5 minutes to obtain the corrosion-resistant steel slag modified steel structure fire retardant coating.

[0039] Comparative Example 1: In this comparative example, the raw material ratio of a steel structure fire retardant coating is calculated by weight as follows: 150 parts of bonding material, 360 parts of lightweight refractory material, 51.3 parts of flame retardant material, 7.5 parts of anhydrous sodium sulfate, 180 parts of VAE latex, 480 parts of tap water and 13.5 parts of thermal stabilizer.

[0040] The bonding material consists of 120 parts of slag and 30 parts of cement.

[0041] The lightweight refractory material is composed of 129.6 parts of expanded vermiculite, 118.8 parts of expanded perlite and 111.6 parts of fly ash hollow microspheres.

[0042] The flame retardant material consists of 51.3 parts of aluminum hydroxide.

[0043] The heat stabilizer consisted of 13.5 parts of hydrotalcite.

[0044] In this comparative example, a fire retardant coating for steel structure is prepared according to the following steps: Step 1: Weigh 120 parts of slag, 30 parts of cement, 7.5 parts of anhydrous sodium sulfate, 129.6 parts of expanded vermiculite, 118.8 parts of expanded perlite, 111.6 parts of fly ash hollow microspheres, 51.3 parts of aluminum hydroxide, and 13.5 parts of hydrotalcite, and put them into a mixer in sequence, and adjust the mixer speed to 140 r / min, stir and mix at room temperature for 2 min to make them evenly mixed to obtain component A; Step 2: Weigh 480 parts of tap water and 180 parts of VAE latex, stir and mix at room temperature at a speed of 140-200 r / min for 2 min to uniformly mix the materials to obtain component B; Step 3: Pour component B into component A and stir for 5 minutes to obtain the steel structure fire retardant coating.

[0045] Comparative Example 2: In this comparative example, the raw material ratio of a steel slag modified steel structure fire retardant coating is as follows by weight: 105 parts of bonding material, 360 parts of lightweight refractory material, 51.3 parts of flame retardant material, 7.5 parts of anhydrous sodium sulfate, 180 parts of VAE latex, 480 parts of tap water, 9 parts of benzotriazole, 45 parts of anti-shrinkage agent and 13.5 parts of thermal stabilizer.

[0046] The bonding material consists of 75 parts of slag and 30 parts of cement.

[0047] The anti-shrinkage agent consists of 45 parts of steel slag.

[0048] The lightweight refractory material is composed of 129.6 parts of expanded vermiculite, 118.8 parts of expanded perlite and 111.6 parts of fly ash hollow microspheres.

[0049] The flame retardant material consists of 51.3 parts of aluminum hydroxide.

[0050] The heat stabilizer consisted of 13.5 parts of hydrotalcite.

[0051] In this comparative example, a steel slag modified steel structure fire retardant coating is prepared according to the following steps: Step 1: Weigh 75 parts of slag, 30 parts of cement, 7.5 parts of anhydrous sodium sulfate, 129.6 parts of expanded vermiculite, 118.8 parts of expanded perlite, 111.6 parts of fly ash hollow microspheres, 51.3 parts of aluminum hydroxide, and 13.5 parts of hydrotalcite, and put them into a mixer in sequence, and adjust the mixer speed to 140 r / min, stir and mix at room temperature for 2 min to make it evenly mixed to obtain component A; Step 2: Weigh 480 parts of tap water and 180 parts of VAE latex, stir at room temperature at a speed of 140-200 r / min and add 45 parts of steel slag, then continue stirring and mixing for 2 minutes to make the materials uniform, to obtain component B; Step 3: Add 9 parts of benzotriazole to component B at room temperature at a speed of 140-200 r / min, and then continue to stir and mix for 2 minutes to make the materials uniform, to obtain component C; Step 4: Pour component C into component A and stir at a speed of 140-200 r / min for 5 min to obtain the steel slag modified steel structure fire retardant coating.

[0052] According to the "Steel Structure Fire Retardant Coating Specification GB14907-2018", the physical and chemical properties of the fire retardant coatings prepared in the embodiments and comparative examples were tested. The testing method is as follows, and the results are shown in Table 1.

[0053] 1. Use the prepared fire retardant coating to cast a prismatic specimen with a size of 40 mm × 40 mm × 160 mm. The specimen has copper heads at both ends. L 0 After that, the specimens were cured in an indoor environment with a temperature of 20±5℃ and a humidity of >70% for 90 days, and the natural drying length was tested. L t , And calculate the drying shrinkage rate according to the formula: ε=( L 0 - L t) / ( L - L d ), where: ɛ is the natural drying yield of the specimen; L 0 is the initial length of the specimen (mm); L t is the length of the specimen at time t (mm); L is the original length of the specimen, i.e. 160 mm;L d It is the sum of the lengths of the copper heads at both ends of the buried specimen, which is 20 mm±2 mm.

[0054] 2. The prepared fire retardant coating was cast into a cubic specimen with a size of 40 mm × 40 mm × 40 mm, and a steel sheet with a size of 30 mm × 40 mm × 2 mm was placed in it, with part of it exposed and the exposed area of ​​1 cm 2 , the R of the specimen was tested using a three-electrode system ct The corrosion resistance is characterized by the open circuit potential and the auxiliary electrode (CE). The reference electrode (RE) is AgCl, and the working electrode (WE) is a 1 cm2 bare electrode. 2 The EIS measurement parameters are: sine wave AC signal 10 mV, frequency 100 kHz~10 mHz. The Tafel curve measurement parameters are: scanning speed 0.01 V / s.

[0055] 3. Apply the prepared fire retardant coating to the surface treated Q235 steel plate with a size of 150 mm × 70 mm × 6 mm, with a coating thickness of 150 mm. After application, place it in an indoor environment with a temperature of 20 ± 5 ℃ and a humidity of > 70 % for 7 days. Use an alcohol torch to continuously burn the coating, and the time required for the temperature on the back of the steel plate to rise to 250 ℃ is used to reflect the fire retardant performance of the coating.

[0056] 4. The prepared fire retardant coating was made into cubic specimens with a size of 70.7 mm × 70.7 mm × 70.7 mm. After curing for 28 days in an indoor environment with a temperature of 20±5 ℃ and a humidity of >70%, the compressive strength of the specimens was tested.

[0057] 5. Pour the prepared fire retardant coating on the central part of a steel sheet substrate with a size of 70 mm × 70 mm. The coating pouring size is 40 mm × 40 mm × 5 mm. Smooth the surface and surrounding areas. After curing for 28 days in an indoor environment with a temperature of 20±5 ℃ and a humidity of >70%, test the bonding strength of the test block.

[0058] Table 1

[0059] As can be seen from Table 1, compared with the fire retardant coating prepared in Comparative Example 1 without adding steel slag, the fire retardant coating prepared in Example 1 with adding steel slag has a smaller drying shrinkage and open circuit potential, and a higher charge transfer resistance R ct, longer fire-resistant time and higher compressive strength and bonding strength, indicating that the addition of steel slag helps to improve the mechanical properties and corrosion resistance of the fire-retardant coating. At the same time, through the comparison of Examples 1 and 2 and Comparative Example 2, it can be seen that the above-mentioned properties of the fire-retardant coating prepared by using expanded perlite modified with benzotriazole are further improved, indicating that adsorbing benzotriazole on the pore wall of expanded perlite can effectively reduce the negative effects that may be produced when benzotriazole is used directly, thereby further improving the comprehensive performance of the coating.

[0060] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. A corrosion-resistant steel slag modified steel structure fire retardant coating, characterized in that: The raw materials and their amounts are as follows by weight: 90-150 parts of bonding material, 320-360 parts of modified lightweight refractory material, 30-60 parts of flame retardant material, 3.75-7.5 parts of anhydrous sodium sulfate, 150-210 parts of VAE latex, 420-480 parts of water, 0-70 parts of anti-shrinkage agent, and 13.5 parts of heat stabilizer; The modified lightweight refractory material is composed of expanded vermiculite, modified expanded perlite and fly ash hollow microspheres in a mass ratio of 36:33:

31.

2. The corrosion-resistant steel slag modified steel structure fire retardant coating according to claim 1, characterized in that: The bonding material consists of slag and cement in a mass ratio of 7:

3.

3. The corrosion-resistant steel slag modified steel structure fire retardant coating according to claim 1, characterized in that: The modified expanded perlite is prepared by soaking dried expanded perlite in a benzotriazole solution with a mass concentration of 2% under vacuum conditions for 30 minutes and then drying for 24 hours; wherein the mass ratio of the expanded perlite to the benzotriazole is 118.8:

9.

4. The corrosion-resistant steel slag modified steel structure fire retardant coating according to claim 1, characterized in that: The flame retardant material is aluminum hydroxide.

5. The corrosion-resistant steel slag modified steel structure fire retardant coating according to claim 1, characterized in that: The anti-shrinkage agent is steel slag.

6. The corrosion-resistant steel slag modified steel structure fire retardant coating according to claim 1, characterized in that: The thermal stabilizer is hydrotalcite.

7. The corrosion-resistant steel slag modified steel structure fire retardant coating according to claim 1, characterized in that: The preparation method comprises the following steps: (1) Preparation of component A: The bonding material, anhydrous sodium sulfate, expanded vermiculite, fly ash hollow microspheres, flame retardant material, and heat stabilizer were stirred and mixed at room temperature at a speed of 140 r / min for 2 min to obtain component A; (2) Preparation of component B: Stir water and VAE latex at room temperature at a speed of 140-200 r / min and add anti-shrinkage agent, then continue stirring and mixing for 2 min to make the materials uniform, thereby obtaining component B; (3) Preparation of corrosion-resistant steel slag modified steel structure fire retardant coating: Stir components A and B at a speed of 140-200 r / min at room temperature and add modified expanded perlite, then continue stirring for 5 min.

Citation Information

Patent Citations

  • Hierarchical pore nano zeolite modified epoxy flame-retardant coating

    CN112625541A

  • Low-shrinkage thermal insulation concrete and preparation method thereof

    CN113929380A

  • Resistance-reducing corrosion-inhibiting composition and preparation method thereof

    CN116230288A

  • High-durability nano reinforced cement-based repair material and preparation method thereof

    CN116354678A

  • Fireproof thermal insulation coating and application thereof

    CN116751471A